Solar photovoltaics value chain and end-of-life management practices: A systematic literature review - Amrollahi Biyouki, Zahra; Zaman, Atiq; Marinova, Dora; Minunno, Roberto; Askari Shayegan, Maryam (MDPI AG, 2024)
Many challenges emerge in the life cycle of solar photovoltaic (PV) panels throughout the processes of their deployment and use in residential, commercial, industrial and transportation sectors. There is a growing need for total product recovery by recycling and reusing the solar panel base and other components in a way that is economically efficient and environmentally sound. This study highlights the urgency to develop and implement a suitable system for the collection and management of photovoltaic systems at their end-of-life cycle and the need for professional implementation of circular strategies in the solar PV value chain. To achieve this goal, a systematic literature review of 81 peer-reviewed articles, published in English between 2013 and 2023, was conducted. The main purpose of the analysis is to examine the value chain of the solar panels covering the period of design, construction, use, end of life, recovery or landfill. The two processes that are investigated include the extent of end-of-life management of PV panels and the extent of circular strategies to reach a sustainable and comprehensive business model. It is argued that the current obstacles faced by solar energy businesses create new opportunities and challenges for innovation within a circular PV industry, and appropriate policies and trained professionals are needed for the implementation of the Sustainable Development Goals (SDGs), including SDG12, in the solar PV value chain.